Intensity level as sustainable energy: Analysis of the conversion of energy stored on cicadas sound waves - Umam, Rofiqul; Palupi, Endah Kinarya; Yakin, Khusnul; Iqbal, Mochamad; Siregar, Rahmat Nawi; Irzaman, Irzaman (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
In this study, the researchers measured cicadas' sound waves, considering that cicadas are mostly found in rural areas. The intensity level meter (AMTAST AMF003) was used with time variations (9:00 JST; 12:00 JST; and 15:00 JST). Measurements of air temperature differences (Krisbow Temperature & Humidity Data Logger) were also carried out, and weather conditions were also considered in data collection using satellite data from Himawari, Japan. The interpretation results of intensity level's trend measured at 3:00 pm JST were decreased concerning the changes in days. Meanwhile, the measurement at 09:00 am and 12:00 pm JST did not show a decrement concerning the changes in days (31 days in total). These results show that temperature changes (towards autumn) can affect the intensity level of sound waves. In addition, slightly different intensity levels can affect large changes in acoustic power or the produced sound.